EggQuality-UFRPE: A Chicken Egg Dataset for Multidisciplinary Studies in Animal Science and Computing - Abreu, Katariny Lima de; Souza, Andréa; Carmo, Matheus; Souza, Lilian Francisco de; Rabello, Carlos Bôa-Viagem; Salvadeo, Denis; Lima, João Paulo; Brito, Kellyton (Anais do Dataset Showcase Workshop (DSW); 2025: Anais do VII Dataset Showcase Workshop, 2025)
This paper presents EggQuality-UFRPE, a multidisciplinary dataset comprising 2,150 chicken egg instances with 29 features, collected through manual measurements using advanced instrumentation. It addresses the scarcity of open-access empirical data in animal science, supporting multidisciplinary research with computer disciplines, such as data science and machine learning. A descriptive analysis is included, reporting mean, median, dispersion metrics, missing data proportions, and Pearson correlation coefficients among features. These statistics reveal the dataset’s internal consistency and support exploratory modeling. Despite limitations, such as a single hen strain, the dataset enables applications ranging from regression and predictive modeling to synthetic data generation and multimodal learning, promoting integration between computational and animal sciences.